How to present at meetings - Robinson, Neville (Chichester, UK : Wiley-Blackwell/BMJ Books, 2012)
Provides a basic framework to give a competent presentation New edition of one of the most popular books in the How To series Foreword by Terry Wogan and a new coeditor Neville Robinson introduce a fresh perspective Includes two new chapters - on advanced Powerpoint and poster presentations
Previous ed.: 2007. Includes bibliographical references and index.
Keywords: Communication in medicine; Business presentations; Medical writing